2018
DOI: 10.20473/ijosh.v7i1.2018.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Jarak Monitor, Durasi Penggunaan Komputer, Tampilan Layar Monitor, Dan Pencahayaan Dengan Keluhan Kelelahan Mata

Abstract: The use of the computer was very support various human activities. Although many of the benefits gained from computer but if we weren’t awareness can cause health problem, such as complaints of eye fatigue. The purpose of this research was to find the relation between distance monitor, duration of computer use, screen display monitor and lighting with complaints of eye fatigue on workers at PT. Indonesia Power UP Semarang. This research was a quantitative research with cross sectional design. Population in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 3 publications
2
10
0
15
Order By: Relevance
“…This research was supported by Putri and Mulyono (2018) that from the results of the study there was no significant relationship between lighting and eye fatigue with a value of p=1.000. In the research, it was found that almost all workers who had good or poor lighting had eye fatigue complaints.…”
Section: The Relation Between General Lighting Intensity and Computermentioning
confidence: 52%
“…This research was supported by Putri and Mulyono (2018) that from the results of the study there was no significant relationship between lighting and eye fatigue with a value of p=1.000. In the research, it was found that almost all workers who had good or poor lighting had eye fatigue complaints.…”
Section: The Relation Between General Lighting Intensity and Computermentioning
confidence: 52%
“…Oleh karena itu, diperlukan penerangan yang cukup memadai untuk mengurangi terjadinya keluhan kelelahan mata. ketika seseorang bekerja di depan komputer dengan pencahayaan kurang dari 300 lux, maka ia memiliki risiko mengalami keluhan kelelahan mata sebesar 10,7 kali lebih besar dibandingkan dengan seorang pekerja pengguna komputer dengan pencahayaan sama atau lebih dari 300 lux (7). Berdasarkan hasil studi pendahuluan yang dilakukan di Universitas Respati Yogyakarta pada tanggal 15 Juli 2020 dari 6 http://formilkesmas.respati.ac.id responden yang bekerja pada ruangan perpustakaan, Biro SDM , Keuangan, dan BKACC yang dilakukan wawancara terdapat pekerja mengalami keluhan kelelahan mata mata saat bekerja seperti mata merah, mata teras perih, mata berair], penglihatan kabur dan sulit fokus saat melihat dengan durasi kerja < 8 jam dan rata-rata penggunaan computer selama > 4 jam sehari.…”
Section: Pendahuluanunclassified
“…Intensitas cahaya yang ideal untuk bekerja di depan komputer adalah 200-700 lux (Saputro, 2013). Ketika seseorang bekerja di depan komputer dengan pencahayaan kurang dari 300 lux, maka ia memiliki risiko mengalami keluhan kelelahan mata sebesar 10,7 kali lebih besar dibandingkan dengan seorang pekerja pengguna komputer dengan pencahayaan sama atau lebih dari 300 lux (Budiono et al, (2008) dikutip dalam (Putri & Mulyono, 2018).…”
Section: Gambar 2 Prevalensi Partisipan Yang Mengalami Gejalaunclassified